Dexmedetomidine-assisted drug interviews: an observation in psychiatric setting - Goswami, Devalina (BMJ Case Rep, 2018)
Drug-assisted interviews are an effective tool in the management of various psychiatric illnesses where psychopharmacological, as well as routine psychological interventions, do not prove beneficial. These have most commonly been done by using barbiturates and benzodiazepines that have given favourable results for a long time. However, they carry the risk of respiratory depression and difficulty in maintaining the plane of sedation where the patient is amenable to interviewing. In our experience of drug-assisted interviews with two patients we used intravenous dexmedetomidine, which is being used in anaesthesia practice for conscious sedation or sedation in the intensive care unit. We found dexmedetomidine to be superior to thiopentone in achieving a level of conscious sedation where the patients were amenable for an interview, with no significant adverse events and faster post-anaesthetic recovery.